Optimasi Kedalaman Pump Intake pada Sistem Sucker Rod Pump Sumur WDHA-01 Berdasarkan Analisis Submergence dan Inflow Performance Relationship - Hosyan Emanuel Mangiri; Risna Risna (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Well WDHA-01, producing from the J-2b and J-5 zones, has experienced a decline in productivity due to reservoir pressure depletion, with a static bottomhole pressure (SBHP) of 773 psi and a flowing bottomhole pressure (FBHP) of 0 psi. This practical training project aims to determine the optimal pump intake depth for a sucker rod pump (SRP) system using the Inflow Performance Relationship (IPR) based on the Vogel method and submergence analysis. The analysis results indicate a productivity index (PI) of 0.08634 bbl/psi-day and an Absolute Open Flow Potential (AOFP) of 67 BFPD. The current pump submergence is only approximately 2 meters, which is significantly below the required minimum submergence of 23.4 meters, thereby increasing the risk of gas lock and cavitation. The calculation of the optimal pump intake depth, considering the bottom perforation depth, optimal submergence, and an appropriate safety factor, resulted in a recommended setting depth of 636 mTVD, or 26 meters deeper than the current pump setting. Repositioning the pump to this depth is recommended to improve fluid flow stability and extend the operational service life of the pump.